The East India Company and the pirates of the Persian Gulf from the first punitive expedition to the signing of the General Maritime Treaty - Pierzchała, Andrzej (Saeculum Christianum. Pismo Historyczne, 2021)
Although almost every sea was dominated by Royal Navy, it couldn't reach every single place in the world. Trade company's ships and fully armed merchant ships many times had to take care of themselves. The East India Company had an independent policy that goes beyond the subcontinent. During the first decade of 19th century, the most difficult problem to solve (except the problems of India) was the Persian Gulf, which appeared to be the source of many profits and problems, that wasn't easy to solve and took a lots of time to conclude. The Treaty of 1820 solved the problems of sea and overland campaigns. The times before signing the agreement and the way, it was created are included in this article.